Influence of different agroforestry systems on yield and nutrient uptake in semi-arid region of Haryana - Dahiya, Garima; Dahiya, Garima; Bhardwaj, K.K.; Devi, Sonia; Ahlawat, Isha; Singh, Charan; Dhillon, R.S. (Indian Journal of Agroforestry, 2023)
Agroforestry system is one of the most promising land use system which not only influences the soil properties, dynamic soil biodiversity but also maintains the agricultural sustainability. The present study was conducted at the research farm, department of forestry, CCS HAU, Hisar to ascertain the effect of different agroforestry system on nutrient content, uptake and yield in semi-arid region of Haryana. Nutrient content i.e. N and P in grain, N in straw and micronutrient (Zn, Fe, Mn and Cu) in both grain and straw was non-significant among different agroforestry system. Maximum nutrient uptake i.e. N, P, K and micronutrient (Zn, Fe, Mn and Cu) in both grain and straw was obtained under sole wheat crop. Yield declined under all the agroforestry systems as compared to sole cropping. Under Poplar + wheat and Melia + wheat, both grain and straw yield reduced by 10.6%; 13.2% and 17.8%; 16.3%, respectively as compared to sole wheat crop. Similarly, grain as well as straw yield reduced by 5.0% and 6.8% under Eucalyptus + barley system, respectively.Â Shisham + mustard agroforestry system also recorded decline in both grain and straw yield by 22.2% and 20.0%, respectively. Â